Early versus late thrombolysis in acute arterial occlusion of lower extremity. (1st February 2017) - Moon, Hyun Gee; Cho, Sang Cheol; Jeong, Sang Woo; Lee, Gyu Ik; Jo, Young Eun; Youn, Boram; Kang, Won Yu; Hwang, Sun Ho; Kim, Wan; Kim, Weon
Abstract: Background: Acute arterial occlusion in lower extremity is an urgent condition which occurs when there is an abrupt interruption of blood flow into an extremity. Reperfusion through early intervention can increase limb salvage and decrease mortality. There was no common agreement when is the best to start thrombolysis in treating acute arterial occlusion. This study was designed to study the efficacy of an early thrombolysis compared with a late thrombolysis. Method: We identified all patients discharged from the Gwangju Veterans hospital with a diagnosis of acute arterial occlusion between 2006 and 2014. 72 patients were eligible, and every patient had treated with catheter-directed thrombolysis on the day or 1 day after admission. Among them, 42 patients had undergone an early thrombolysis (less than 7 days after the onset of symptoms) and the other 30 patients had undergone a late thrombolysis (more than 7 days after the onset of symptoms). The primary outcome was amputation rate at 6 months. The secondary outcomes were all cause mortality at 6 months and increase of ankle brachial index (ABI). Results: Amputation rate at 180 days in the early thrombolysis group was 7.1% as compared with 30% in the late thrombolysis group. All cause mortality at 6 months and increase of ABI were not different between two groups. In multivariable Cox-regression analysis, late thrombolysis was independent predictor of amputation at 6 months. Conclusion: Early thrombolysis was superior in preventing amputation than late thrombolysis.